2004
DOI: 10.1023/b:hrev.0000011391.81676.3c
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Remodeling in Viral Heart Disease: Possible Interactions Between Inflammatory Mediators and MMP-TIMP System

Abstract: Matrix metalloproteinases (MMP), a family of proteases, are involved in the degradation of extracellular matrix proteins and hence in the determination of interstitial architecture. In the heart, MMPs have been found to play a significant role in the development of myocardial remodeling and congestive heart failure. Tissue inhibitors of matrix metalloproteinases (TIMPs) represent a family of proteins which are known to regulate the expression and activity of MMPs. TIMPs are endogenous physiological inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 112 publications
2
31
1
Order By: Relevance
“…22 Conversely, adenovirus-mediated expression of TIMP-1 was reported to mitigate the severity of ischemic injury. 39 These data suggested that TIMP-1 might exert a protective effect in the myocardium, consistent with the concept that increased MMP activity is a key process driving myocardial pathology after myocardial infarction or stress-related injuries 13,32 ; by this reasoning, expression of TIMP-1 is a physiological response that counterbalances MMP proteolysis, 14,40,41 and TIMP-1 blockade should, in theory, exacerbate disease. We show here that TIMP-1 expression in the heart increases during viral myocarditis, consistent with many studies that show that TIMP-1 is up-regulated in response to myocardial injury.…”
Section: Discussionsupporting
confidence: 68%
“…22 Conversely, adenovirus-mediated expression of TIMP-1 was reported to mitigate the severity of ischemic injury. 39 These data suggested that TIMP-1 might exert a protective effect in the myocardium, consistent with the concept that increased MMP activity is a key process driving myocardial pathology after myocardial infarction or stress-related injuries 13,32 ; by this reasoning, expression of TIMP-1 is a physiological response that counterbalances MMP proteolysis, 14,40,41 and TIMP-1 blockade should, in theory, exacerbate disease. We show here that TIMP-1 expression in the heart increases during viral myocarditis, consistent with many studies that show that TIMP-1 is up-regulated in response to myocardial injury.…”
Section: Discussionsupporting
confidence: 68%
“…22 In addition to their role in modulating lymphocyte function, these proinflammatory cytokines also disturb the balance between MMPs and TIMPs, which results in overall increased MMP activity. 11 Reduced cytokine expression in the absence of uPA may also have resulted from a reduced number of inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of the uPA gene impaired wound healing after acute myocardial infarction 6 and prevented pressure overload-induced cardiac failure, 7 whereas absence of MMP-2 or MMP-9 prevented cardiac rupture 6,8 and dilatation 9 after myocardial infarction. A single study showed increased transcript levels of MMP-9 together with decreased transcript levels of tissue inhibitor of metalloproteinases (TIMP)-1 and TIMP-4 during CVB3-induced myocarditis 10 (reviewed in Pauschinger et al 11 ). Given the possible importance of the cardiac matrix in myocarditis, the present study aimed to investigate whether increased expression of the proteolytic enzymes uPA and MMPs may mediate acute inflammation and cardiac dilatation during CVB3-induced viral myocarditis.…”
Section: Clinical Perspective P 573mentioning
confidence: 96%
See 1 more Smart Citation
“…33 It has been shown that leukocytes express high levels of TIMPs, 32 and a decrease in TIMP expression can yield a net increase in MMP activity. 34 Therefore, it was determined whether low levels of H 2 O 2 such as those generated by VCAM-1 signaling could modulate MMP and TIMP expression in the resting splenic lymphocytes. Lymphocytes were incubated in the presence of 1 M H 2 O 2 for 0, 0.25, or 5 hours.…”
Section: Lymphocyte Mmp-9 Activation Is Blocked By Inhibition Of Endomentioning
confidence: 99%